Mapping organization culture with complex multi-level models - Kiril Dimitrov (Vanguard Scientific Instruments in Management, 2013)
The current article reviews complex multi-level frameworks as a modern and complicated technique of describing target organizational cultures. The essence, reasons of development, advantages and disadvantages and comparisons of/among the items in a set of ten frameworks, containing at least four organization culture levels, are revealed here. A system of classifying these elaborated frameworks is proposed and substantiated, too. The issues, concerning teaching of such models at economic universities in the presence of different types of audiences, are discussed and some appropriate solutions are also suggested.
Keywords: M14; Z10; 330; organization culture; cultural levels; firm culture; corporate culture; multi-level cultural models